مقاربة في تحليل الآثار على متغيرات كلية مختارة: An approach to analyzing the effects on selected total variables (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The management of the external debt and the way it is used reflects the ability of the economic management in all its aspects, financial, monetary, and commercial, to make the loan productive and able to meet the requirements of distributing the burden of obligation between the present and future generations. As far as the Iraqi economy, after 2003 is concerned, it did not suffer from a resource gap, as a developmental concept, and resorting to external borrowing was due to the fragility of the economy and the failure of development efforts and the management of the public budget resources to protect the economy in times of crisis and the failure to exploit the revenue increases achieved when oil prices were high, to cement creditworthiness. Accordingly, resorting to external borrowing should take into account the criteria of development sustainability and what this requires to engage in real reforms in the structure of the Iraqi economy, especially other productive sectors other than the oil sector.